Virtual and Augmented Reality Technologies to Enhance Tourists’ Knowledge of Rural Tourism Destinations - Raj Kumar, Anil Kumar, Harpreet Singh (Mathematical Statistician and Engineering Applications, 2023)
The world acknowledges that rural tourism has a significant positive impact on society. Additionally, rural tourism contributes to the improvement of the community’s social fabric. Developing intelligence, a growing desire to learn, and rural knowledge were the primary determinants. The purpose of this paper is to examine the applicability of augmented and virtual reality to rural tourism. Despite the importance of virtual reality and augmented reality for understanding the tourist experience being emphasized in a number of studies, there have been no previous efforts to improve tourism knowledge in rural tourism. In an effort to theoretically examine the knowledge of tourists in rural tourism, this study examines the effects of augmented reality and virtual reality technologies on the visitor experience.This study contributes to the fields of virtual reality and augmented reality through its comprehensive approach to development.